2019
DOI: 10.1186/s13068-019-1527-3
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable process for procuring biologically active fractions of high-purity xylooligosaccharides and water-soluble lignin from Moso bamboo prehydrolyzate

Abstract: Background Prehydrolyzate, which is from the prehydrolysis process in dissolving pulps industry, contains various sugar-derived and lignin compounds such as xylooligosaccharides (XOS), gluco-oligosaccharides, xylose, glucose, and soluble lignin (S-L). The XOS has several beneficial effects on human physiology. XOS and S-L in prehydrolyzate are difficult to efficiently fractionate due to their similar molecular weights and water solubility. In this work, we proposed a sustainable and green process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(88 citation statements)
references
References 49 publications
2
84
0
2
Order By: Relevance
“…After 3 h, the intracellular ROS levels of ERM-CZ-100-treated HDF cells were evaluated by DCF-DA assay following the protocol described previously [43,44]. After 24 h, the viabilities of ERM-CZ-100-treated HDF cells were measured by MTT assay according to the methods described previously [45,46].…”
Section: Determination Of the Effect Of Dphc On Pm-induced Cytotoxicimentioning
confidence: 99%
“…After 3 h, the intracellular ROS levels of ERM-CZ-100-treated HDF cells were evaluated by DCF-DA assay following the protocol described previously [43,44]. After 24 h, the viabilities of ERM-CZ-100-treated HDF cells were measured by MTT assay according to the methods described previously [45,46].…”
Section: Determination Of the Effect Of Dphc On Pm-induced Cytotoxicimentioning
confidence: 99%
“…The spectra were monitored in a transmittance band mode in the range 400 ~ 4000 cm − 1 . Two-dimensional proton-detected heteronuclear single quantum (2D HSQC) spectrum of the samples was recorded to provide structural information of XOS [28]. First, 40 mg of sample were dissolved in 0.5 mL DMSO-d 6 and then added to 5 mL NMR tube to exploit the 2D-HSQC spectra of the samples using a standard Bruker HSQC pulse sequence.…”
Section: Analysis Of Dried Phl Samplesmentioning
confidence: 99%
“…The average reduced elastic modulus of the S 2 layer was 5.28 GPa and the hardness was 0.25 GPa, which was lower than that of softwood (6.55-27.5 GPa) and hardwood (16.9-24.6 GPa) [11], but higher than that of cotton fibers (4 GPa) [23] and kapok fibers (2 GPa) [41]. Huang et al [49,50] found that the reduced elastic modulus of bamboo fiber cell walls in the transverse direction was 5.91 GPa, and in the longitudinal direction, was 17.6 GPa, and the hardness was 0.37 GPa. The samples were embedded in epoxy resin, which might result in undesirable chemical modifications caused by epoxy impregnation [50,51].…”
Section: In Situ Nanoindentationmentioning
confidence: 99%